Efficacy of a feed additive consisting of endo‐1,4‐beta‐xylanase and endo‐1,3(4)‐beta‐glucanase produced with Talaromyces versatilis IMI 378536 and DSM 26702 (ROVABIO® ADVANCE) for weaned piglets (Adisseo France SAS) - EFSA Panel on Additives and Products or Substances used in Animal Feed (FEEDAP); Vasileios Bampidis; Giovanna Azimonti; Maria de Lourdes Bastos; Henrik Christensen; Mojca Durjava; Birgit Dusemund; Maryline Kouba; Marta López‐Alonso; Secundino López Puente; Francesca Marcon; Baltasar Mayo; et al. (EFSA Journal)
Abstract Following a request from the European Commission, the Panel on Additives and Products or Substances used in Animal Feed (FEEDAP) was asked to deliver a scientific opinion on the efficacy of ROVABIO® ADVANCE (liquid and solid) which contains endo‐1,4‐beta‐xylanase and endo‐1,3(4)‐beta‐glucanase produced with Talaromyces versatilis IMI 378536 and DSM 26702 as a zootechnical feed additive for weaned piglets at the recommended use level of 1800 U xylanase and 1250 U glucanase per kg feed. In a previous assessment, three long‐term trials in weaned piglets were submitted. Two of them were considered to support the efficacy of the additive while a third trial was not further considered due to the large number of veterinary treatments applied. A new trial was provided to support the efficacy of the additive, but it did not show a significant improvement of the performance parameters at the minimum recommended use level. Due to the lack of sufficient data, the FEEDAP Panel is not in the position to conclude on the efficacy of the additive for the target species.